2024
DOI: 10.1146/annurev-med-043021-033114
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Diabetic Neuropathy: New Insights in Diagnosis and Treatment

Brendan R. Dillon,
Lynn Ang,
Rodica Pop-Busui

Abstract: Diabetic neuropathy is a highly prevalent complication of diabetes. It consists of a broad range of neuropathic conditions, such as distal symmetric polyneuropathy and various forms of autonomic neuropathies involving the cardiovascular, gastrointestinal, and urogenital systems. Prevention or diagnosis in early stages of disease is crucial to prevent symptomatic onset and progression, particularly in the absence of current disease-modifying therapies. In this review, we describe the four main types of diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…For this reason, it is uncertain how Bell's palsy and these CMRs are related; either the detectable CMRs are causes or merely associated disorders of Bell's palsy. However, it was suggested that the prediabetes state was possibly an associated disorder with Bell's palsy, especially among those who have characteristics of MS or a personal history of diabetes risks [2,37,38]. Moreover, a study of the genetic association between HT and Bell's palsy also reported that HT was a significant risk of Bell's palsy at the genetic level, whereas DM and lipid disorders required further studies for confirmation [39].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is uncertain how Bell's palsy and these CMRs are related; either the detectable CMRs are causes or merely associated disorders of Bell's palsy. However, it was suggested that the prediabetes state was possibly an associated disorder with Bell's palsy, especially among those who have characteristics of MS or a personal history of diabetes risks [2,37,38]. Moreover, a study of the genetic association between HT and Bell's palsy also reported that HT was a significant risk of Bell's palsy at the genetic level, whereas DM and lipid disorders required further studies for confirmation [39].…”
Section: Discussionmentioning
confidence: 99%
“…autonomic dysfunction, however, affects the autonomic nervous system that regulates involuntary bodily functions. This dysfunction contributes to various problems, such as cardiovascular dysfunction characterized by blood pressure and heart rate changes, gastrointestinal dysfunction leading to gastroparesis, and urogenital dysfunction affecting bladder control and sexual function ( 2 ). DPN alone contributes to more than $10 billion in annual healthcare expenses, exceeding one-fourth of the total direct medical costs of diabetes ( 3 ).…”
Section: Introductionmentioning
confidence: 99%